2022
DOI: 10.1590/2175-8239-jbn-2022-0013en
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury outcomes in covid-19 patients: systematic review and meta-analysis

Abstract: Background: Acute kidney injury (AKI) is a frequent complication of coronavirus-19 disease (COVID-19). Therefore, we decided to perform a systematic review and meta-analysis with data from the literature to relate the development of COVID-19 associated-AKI with comorbidities, medications, and the impact of mechanical ventilation. Methods: We performed a systematic review using the Newcastle-Ottawa scale and a meta-analysis using the R program. Relevant studies were searched in the PubMed, Medline, and SciELO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 86 publications
0
4
0
1
Order By: Relevance
“…In three different studies carried out by Cheng, Li, and Ng on AKI in COVID-19 patients, the incidence of AKI was reported to be between 5.4% and 39.9%, and mortality in these patients was 30% to 40% (22)(23)(24). Moreover, Silva et al, in a systematic review, reported an incidence rate of 31% for AKI, and the mortality of 39.2% in these patients (25). Although the AKI incidence rate in our study was compatible with their findings, the mortality rate was higher.…”
Section: Discussionmentioning
confidence: 96%
“…In three different studies carried out by Cheng, Li, and Ng on AKI in COVID-19 patients, the incidence of AKI was reported to be between 5.4% and 39.9%, and mortality in these patients was 30% to 40% (22)(23)(24). Moreover, Silva et al, in a systematic review, reported an incidence rate of 31% for AKI, and the mortality of 39.2% in these patients (25). Although the AKI incidence rate in our study was compatible with their findings, the mortality rate was higher.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, we did not see any significant difference in AKI requiring dialysis. This shows that AKI in IBD is usually self-limited and likely due to volume depletion, as seen in the general population [ 27 ]. Therefore, timely volume resuscitation is vital in preserving renal function, especially in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 These results differ from those of some systematic reviews that show a lower incidence and higher mortality particularly in ICU patients worldwide. 12,13 This difference could probably be related to the delayed medical care caused by the saturation of Peruvian hospitals during the first and second waves of the pandemic and the prioritization of ICU admission of patients with better prognosis. 14 Similar to other countries in Latin America, in Peru, hospitalized patients with AKI in need of dialysis most frequently receive hemodialysis (HD) given the little availability of continuous renal replacement therapy (CRRT), prolonged intermittent renal replacement therapy, or peritoneal dialysis (PD) even for critically ill patients.…”
Section: Epidemiology Of Aki In Perumentioning
confidence: 99%
“… 11 These results differ from those of some systematic reviews that show a lower incidence and higher mortality particularly in ICU patients worldwide. 12 , 13 This difference could probably be related to the delayed medical care caused by the saturation of Peruvian hospitals during the first and second waves of the pandemic and the prioritization of ICU admission of patients with better prognosis. 14 …”
Section: Epidemiology Of Aki In Perumentioning
confidence: 99%